MENINGKATKAN KEMAMPUAN SPASIAL MATEMATIS SISWA DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA - Rani Sugiarni; Egi Alghifari; Ayuni Rizka Ifanda (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
Students’ spatial ability of MA Al-Hanif is very low. This is because the students rarely use mathematics learning media which helps learning process. One of learning media that can help imagination is Geogebra. This study aims to determine the improvement of mathematical spatial abilities of students with problem-based learning model assisted with Geogebra. The research method used is Classroom Action Research which implemented in 3 action cycles. Population in this study is students of class XI MA Al-Hanif in academic year 2016-2017, with sample as many as 17 people with Geometry course. The instrument used a matter of spatial ability test in each cycle, teacher and student observation sheet used in learning and student attitude questionnaire. The results showed that, by applying the learning model of problem-based learning problem assisted geogebra can improve spatial ability of the students. This is shown by the results of spatial ability tests in each cycle. In the cycle I, the classical absorption of students reaches 53%, the second cycle action goes up the classical absorption of 76% students and the third cycle action almost 82% of the classical absorption increases from the results of the study concluded that the problem-based learning model assisted geogebra can improve the students’ spatial ability. Furthermore, student and teacher activity toward geogebra assisted Problem-Based Learning model went run effectively and conducive. The response of students in geometry learning with Geogebra assisted problem-based learning model generally produces a positive impression.